Analisa Produksi Panas Radiogenik, Densitas dan Kecepatan Seismik dari Singkapan Batu Granit Panas Bumi Nyelanding, Bangka Selatan - Rahmat Nawi Siregar; Maria Evalina Purba; Ahmat Munawir Siregar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the analysis of radiogenic heat production, density and seismic velocity of the outcrops of the South Bangka Nyelanding geothermal rock. The X-ray Fluorescence (XRF) method is applied to obtain heat-carrying radioactive elements in the form of Uranium, Thorium and Potassium and other oxides which are useful for studying seismic density and velocity. The main oxides used in this study were SiO2, TiO2, Al2O3, MgO, CaO, K2O and P2O5. The results showed that the density increased from the composition of the mineral felsic (acid) - mafic (base). Conclusion, as for the relationship with heat production, the SiO2 and P2O5 elements experienced a significant decrease compared to other oxides. As for seismic velocity, the results show that seismic velocity has a strong correlation with density. Keywords: Radiogenic Heat Production, Seismic Velocity, Density, Oxides